Der Verein Deutsche Sprache - Wirth, Karoline (Bamberger Beiträge zur Linguistik, 2008)
Attempts to keep the German language free from the influence of other languages go back a long way. The influence of English and criticism of Anglicisms have re-entered public discourse in recent years. The current trend towards the renewed founding of language associations can be viewed as a new phase of linguistic purism in Germany. The largest group opposed to the use of Anglicisms in German is the Dortmund-based Verein Deutsche Sprache (VDS), which was founded in 1997. The VDS can now look back on over ten years of its history. During this time, the association has metamorphosed from a minor grouping into an influential association with more than thirty-one thousand members in over seventy countries. Its founder, statistics professor Dr. Walter Krämer, has remained chairperson of the association from its beginnings. This current portrait of the VDS examines the emergence, the organization and the activities of the association against the wider background of the discussion of loan words and the work of other language associations in Germany. To this end, literary sources were evaluated comprehensively, as were the entire contents of the archive of the association´s head office in Dortmund and the personal archive of the initiator of the VDS from the point when the association was founded. The analysis encompassed the period up to 2009. The VDS aims to counteract the spread of Anglicisms in German, and to heighten awareness of the topic in media, politics and business circles. The activities of the association, described in detail in the present study, include organized events, particularly on the "German Language Day" initiated by the association, publications such as the association´s magazine, public lectures, correspondence, media relations and award ceremonies. It is notable that the work of the association is often characterized by a strongly emotional attitude towards the German language. The present study also concerns itself with the question of how the association - in the opinion of the members - defines which Anglicisms should be resisted. No firm consensus on this issue exists within the organization. The association sees itself as a citizen´s initiative and not as an exclusive academic club. The members are reluctant to classify themselves as linguistic purists, although their aims clearly include ridding the language of undesirable elements. The present study demonstrates that the association can clearly be seen as a purist group, since arguments and attitudes found in purist discourse, which were perceived as having been entirely absent from the discussion in Germany over many years, have been revived and used to stimulate the debate on Anglicisms afresh. The results of the present study document that the VDS is characterized by active public relations and a high level of internal activity. This suggests that the VDS may well have consolidated its role as spearhead in challenging Anglicisms still further by now. Its reputation for being in the vanguard in this area would appear to have been earned. It can be assumed that the activities of the association will leave their mark in the medium or long term. What is more significant, however, is that the resonance which these activities find in the media has considerable influence on public discourse.